Ricardo Palma: Art and narrative style when rewriting his short stories - Huárag Álvarez, Eduardo (2020)
In this essay we will assess the validity of Ricardo Palma’s Peruvian Traditions. We note the importance of creating a format that inserts a historical paragraph, as a way of establishing a recreation that is based on events that have occurred. On the other hand, we delve into the careful rewriting work that the narrator does from the stories of the chroniclers. Through the analysis of three traditions, we compare the chronicles with Palma’s stories to highlight their creativity in recreating the events, encouraging possible dialogues, and managing narrative intensity so that interest in reading does not wane.